Emerging markets yield curve dynamics - Morita, Rubens Hossamu (2007)
This work extendes Diebold, Li and Yueís (2006) about global yield curve and proposes to extend the study by including emerging countries. The perception of emerging market su§ers ináuence of external factors or global factors, is the main argument of this work. We expect to obtain stylized facts.that obey similar pattern found by those authors. The results indicate the existence of global level and global slope factors. These factors represent an important fraction in the bond yield determination and show a decreasing trend of the global level factor low ináuence of global slope factor in these countries when they are compared with developed countries. Keywords: Kalman Filter, Emerging Markets, Yield Curve, and Bond.